Arctic falcons population monitoring data - Arctic Falcon Specialist Group (Zenodo, 2020)
The Arctic Falcon Specialist Group (AFSG) is an informal network of biologists with a research focus on Arctic-breeding peregrine falcons ( Falco peregrinus ) and gyrfalcons ( Falco rusticolus) . AFSG was established to enhance the coordination and collaboration on the monitoring of the two Arctic falcon species and the initial joint effort was to compile the first overview of Arctic falcon monitoring sites, present trends for long-term occupancy and productivity, and summarize information describing abundance, distribution, phenology and health of the two species – based on data for 24 falcon monitoring sites across the Arctic. The analyses were published in the journal Ambio (Franke et al. 2020) as a contribution to the terrestrial Circumpolar Biodiversity Monitoring Programme (CBMP) defined by Arctic Council’s Biodiversity Working Group (Christensen et al. 2018). The data compiled from across the Arctic for the analyses by Franke et al. (2020) are here made available for wider usage and comparisons. However, for the analyses in the Ambio paper, some filtering procedures were applied (e.g. time series shorter than 10 sampling years, or fewer than 10 territories monitored), excluding some of the original data that are now made available in this dataset. In addition, some co-authors preferred either to conduct separate uploads of respective data, or declined the invitation to make the data publicly available (see attached map overview of monitoring sites); hence this dataset does not exactly match the data analysed by Franke et al. (2020). This data set contains the annual estimates of peregrine and gyrfalcon ‘occupancy’ and ‘productivity’ in respective monitoring sites; for definitions as well a discussion of challenges in determining, interpreting and comparing those figures across sites with different sampling procedures please consult Franke et al. (2020 and 2017). The file named Arctic falcons monitoring data - AFSG 2020.csv contains the annual estimates of occupancy and productivity for peregrine falcon and gyrfalcon along with information on monitoring sites and the principal investigators as specified in the file ReadMe_Arctic-falcons-monitoring-data.txt . Arctic falcons monitoring data - AFSG 2020.xlsx contains the same data in Microsoft Excel format. The file named AFSG-MonitoringSites-with-data.png provides an overview of the 24 monitoring sites described in Franke et al. (2020) with indication of which datasets are included here. Please note that: The dataset contains information on sample size (number of nesting territories surveyed in each monitoring site and year) for some areas only; for areas without sample size more than 10 territories were usually surveyed. However, for interpreting the data, potential users may need to consult the principal investigators for the specific monitoring sites. The dataset lists the principal investigators (and contact details) as respective “data owners”; in addition to the Creative Commons License 4.0 specifications covering this data upload, potential data users are strongly encouraged to contact the data owners prior to using or interpreting the data – for consent and possible co-authorship. : The dataset lists the principal investigators (and contact details) as respective "data owners"; in addition to the Creative Commons License 4.0 specifications covering this data upload, potential data users are strongly encouraged to contact the data owners prior to using or interpreting the data – for consent and possible co-authorship. : {"references": ["Christensen, T., S. Longan, T. Barry, C. Price, and K. F. L\u00e1russon. 2018. Circumpolar biodiversity monitoring program strategic plan 2018-2021. CAFF Monitoring Series Report No. 29. Conservation of Arctic Flora and Fauna, Akureyri, Iceland.", "Franke, A. Falk, K., Hawkshaw, K., Ambrose, S. Anderson, D.L., Bente, P.J., Booms, T., Burnham, K.K., Carri\u00e8re, S., Ekenstedt, J., Fufachev, I., Ganusevich, S., Johansen, K., Johnson, J.A. Kharitonov, S., Koskimies, P., Kulikova, O., Lindberg, P., Lindstr\u00f6m, B-O., Mattox, W.G., McIntyre, C.L., Mechnikova, S., Mossop, D., M\u00f8ller, S., Nielsen, O.K. Ollila, T., \u00d8stlyngen, A., Pokrovsky, I., Poole, K., Restani,M., Robinson, B.W., Rosenfield, R., Sokolov, A., Sokolov, V., Swem, T. & Vorkamp, K. (2020). Status and trends of circumpolar peregrine falcon and gyrfalcon populations. Ambio 49: 762\u2013783 https://doi.org/10.1007/s13280-019-01300-z", "Franke, A., K. Steenhoff, and C. L. McIntyre. 2017. Terminology. In Applied raptor ecology: essentials from gyrfalcon research, ed. D. L. Anderson, C. M. McClure, and A. Franke, 33-42.\u00a0 Boise, Idaho, USA: The Peregrine Fund."]}